Tax professionals’ perceptions toward tax authority: Ways to strengthen the Malaysian tax administrative system - Abdul Manaf, Nor Aziah (College of Law, Government and International Studies, Universiti Utara Malaysia, 2013)
This article examines tax professionals’ perceptions toward services provided by the tax authority, i.e. Inland Revenue Board Malaysia (IRBM).Using a survey questionnaire, the views of the tax professionals on twelve aspects of the IRBM services were analysed. E-filing system is perceived to be the most efficient service provided by the IRBM while the least efficient service is related to bureaucracy.Comments from tax professionals offer rooms for collaboration with the IRBM in improving the IRBM services specifically related to different environment faced by tax professionals in completing their daily tasks.It is hoped that this study also leads to increase understanding between tax professionals and the IRBM.